Perceived Parental Acceptance-Rejection, Family-Related Factors, and Socio-Economic Status of Families of Adolescent Heroin Addicts - Glavak, Renata; Kuterovac-Jagodić, Gordana; Sakoman, Slavko (2003)
Aim. To compare adolescent heroin addicts and non-addicts with respect to their perceived parental acceptance and rejection, family factors (structure of the family, parents’ marital status, and psychopathological disorders in the family), socio-economic status, and subjective appraisal of their family relations. Methods. Fifty-two heroin addicts aged between 17 and 21, were compared with a group of 52 non-addicts of the same age. The comparison group was selected from an ad-hoc sample of high-school juniors and seniors and first- and second-year university students. Only participants who reported never to have taken any drugs were selected for the group of non-addicts. The perceived parental behavior of mothers and fathers was assessed by the 32-item version of Rohner’ s Parental Acceptance-rejection Questionnaire. Three other questionnaires were constructed to collect information on family factors, socio-economic status, subjective appraisal of family relations, and drug usage. Results. The addicts perceived their mothers as more rejecting (p=0.018 for total score), more aggressive (p=0.007), and showing more undifferentiated rejection (p=0.001) than non-addicts. The addicts perceived their fathers as more rejecting then their mothers (p=0.002 for total score), less warm and accepting (p<0.001), and more neglecting (p=0.001). In comparison with non-addicts, the addicts evaluated the relationships with their mothers (p=0.001) and general satisfaction with their families (p=0.021) as poorer. Adolescent addicts mostly came from intact families. In the addicts’ primary families (mother, father, and siblings), there was significantly higher incidence of addiction (p=0.041), schizophrenia (p=0.022), and suicide or attempted suicide (p=0.012). Addicts’ families belonged to higher income groups then non-addicts (p=0.021). Addicts’ fathers were on average less educated than non-addicts’ fathers (p=0.040) ; typically to a high school level. The education level of addicts’ mothers was similar to that of non-addicts’ mothers (p=0.091), typically they were educated to a high school level. Conclusion. The results of this research indicate the importance of parental rearing practices, especially mothers’ , on adolescent drug abuse and addiction. As addicts perceived their mothers as more rejecting than non-addicts, mothers’ rejection could be one of the major risk factors for developing drug addiction.
Projekt MZOS
Projekt MZOS
ENG